Peningkatan Kualitas Pembelajaran Melalui E-Learning - Elsy Zuriyani (Jurnal Perspektif, 2020)
Peningkatan kualitas pembelajaran terus ditingkatkan dan dipertahakan dengan mengikuti perkembangan zaman. Berhubung zaman sekarang ini penggunaan internet bukan lagi barang baru maka peningkatan kualitas pembelajaran juga dapat dilakukan dengan memanfaatkan internet sehingga proses pembelajaran disebut juga dengan pembelajaran berbasis e-learning. Merupakan sebuah terobosan baru dibidang pengajaran dan pembelajaran, karena mampu meminimalkan perbedaan cara mengajar dan materi, sehingga memberikan standar kulitas pembelajaran yang lebih konsisten. Sistem e-Learning adalah mutlak diperlukan untuk mengantisipasi perkembangan jaman dengan dukungan teknologi informasi dimana semua menuju ke era digital, baik mekanisme maupun konten. The development of information technology in recent years has developed at a very high rate, giving a significant impact on the field of education, thus sparking the birth of the idea of e-learning. To be able to obtain maximum results it is necessary to design an e-learning learning process. The purpose of this writing is the use of the e-learning model in improving the learning process so that it can improve adult learning outcomes. The research method used in the discussion of this paper is the literature study method. The learning model with e-learning is a new breakthrough in the field of teaching and learning, because it is able to minimize differences in teaching methods and materials, thus providing a more consistent quality standard of learning. The e-Learning system is absolutely necessary to anticipate the changing times with the support of information technology where everything is leading to the digital era, both mechanism and content. To be able to produce e-learning that is attractive and desirable in improving the quality of learning, there are three conditions that must be fulfilled in designing e-learning, namely: Simple, simple systems that will make it easier for students to take advantage of existing technology and menus. Personally, teachers can interact well with students, such as communicating in front of the class. Fast, fast, fast response services to the complaints and needs of students, so that learning improvements can be carried out as quickly as possible by the teacher or manager.